Implementation of the Independent Curriculum at State Islamic Junior High School 3, Tasikmalaya City - Nurul Khoirunnisa; Gilman Mawardi; Badrudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The Independent Curriculum is a policy implemented to create more flexible education. This research aims to analyze the implementation of the independent curriculum at Madrasah Tsanawiyah Negeri 3 Tasikmalaya City, including the various challenges faced in implementing the independent curriculum, as well as efforts that can be used to face challenges to optimize its implementation. The research method uses a descriptive qualitative approach. A qualitative approach was used because this research aims to explore and understand phenomena that occur in the field in depth. The research results can provide an overview of curriculum implementation at MTsN 3 Tasikmalaya. In the process of implementing the Independent Curriculum at Madrasah Tsanawiyah Negeri 3 Tasikmalaya, various challenges were faced such as limited resources, resistance to change, and a lack of initial understanding from some teachers. Efforts made to overcome these challenges include intensive outreach, training through workshops and digital platforms such as the Ministry of Religion's Smart Mooc, as well as routine supervision that provides feedback to improve the quality of learning.